Pengaruh Persepsi Konsumen Terhadap Keputusan Pembelian Produk Pertanian Secara Online Pada Masa Pandemi Covid-19 di Kota Gorontalo - Sri Dewi Palamani; Yuliana Bakari; Yuriko Boekoesoe (Sigmagri, 2022)
The objective of this research was to figure out the effect of consumers’ perception (information quality, service quality, convenience, and price) on online purchase decisions for agricultural products during the Covid-19 pandemic in Gorontalo City. This research was conducted in Gorontalo City from December 2021 to February 2022 with a total sample of 96 respondents. The research method employed a quantitative method, while the data analysis used multiple linear regression analysis. The research finding denoted that service quality, convenience, and price partially had a positive and significant effect on the purchase decisions. In the meantime, the information quality partially had a negative and insignificant effect on the value of 2.70, and s significant value was lower than 0.05, indicating that the information quality, service quality, convenience, and the price had a significant effect on online purchase decision for agricultural products during the Covid-19 pandemic in Gorontalo City